Abnormal White Matter Microstructure in Lifelong Premature Ejaculation Patients Identified by Tract–Based Spatial Statistical Analysis. Issue 9 (1st September 2018) - Gao, Ming; Yang, Xuejuan; Liu, Lin; Fei, Ningbo; Xi, Yibin; Guo, Fan; Yan, Fei; Meng, Ping; Yu, Lei; Liu, Peng; Qin, Wei; Yin, Hong; et al.
Abstract: Introduction: Several recent neuroimaging studies have identified functional and structural abnormalities in the cerebral cortex of lifelong premature ejaculation (LPE) patients, including task-related and resting-state brain function, and cortical thickness, although changes in white matter microstructure have not been reported. Aim: To assess the differences in white matter microstructure between LPE patients and healthy controls. Methods: Diffusion tensor imaging (DTI) and tract-based spatial statistical analysis were used to detect differences in white matter microstructure between 32 LPE patients and 32 matched healthy controls. We also analyzed correlations of clinical indices with significant DTI–based features. Main Outcome Measures: DTI–based features (including fractional anisotropy [FA], mean diffusivity, axial diffusivity, and radial diffusivity) were assessed in LPE patients and controls, as well as the correlation of white matter changes in LPE patients with clinical data (including the premature ejaculation diagnostic tool score and the International Index of Erectile Function). Results: LPE patients showed widespread increases in FA and axial diffusivity values compared with controls, including in the right posterior thalamic radiation, posterior corona radiata, bilateral posterior limb of the internal capsule, superior corona radiata, and external capsule. Further, FA in the right posterior thalamic radiation was positively correlated with the premature ejaculation diagnostic tool score in LPE patients. Clinical Implications: Changes of white matter microstructure may be an underlying marker for evaluating sensory conduction efficiency in LPE patients. Strengths & Limitations: There are no previous studies examining white matter microstructure in LPE patients. The present study furthers our understanding of the etiology of LPE. Limitations include a cross-sectional study design without causal information, and no measurement of conduction efficiencies such as cortical somatosensory-evoked potential from the penis, or psychosocial factors. Conclusion: Our findings show potential microstructural white matter abnormalities related to LPE, suggesting that changes in fiber pathways connecting the cerebral cortex and the thalamus may play roles in the etiology of LPE.